Physical and optical traits of tellurite glass: effect of bimetallic TiO2/Au nanoparticles - Auni mardhiah machinin; A. Awang; Fuei, Pien Chee (ResearchGate, 2023)
The dependence of TiO2/Au concentrations on the physical and optical properties of glass was investigated thoroughly. Variations in density, molar volume, molar refraction, refractive index, and polarizability with varying TiO2/Au contents were affected by the formation of non-bridging oxygen. The formation of big islands in the atomic force microscopy image signifies the growth of nanoparticles. The decrement in band gap manifests alteration in the glass network mainly the local field around the Er3+ ions. The rise in Urbach energy illustrates disorder in the glass. The beneficial features of the current glass composition may be useful for photonic devices.